Comunidades de artrópodes em áreas nativas e em sistemas de cultivo - Alvarez, Jonathan Eduardo Cubides (2016)
Modify soil conditions by using tools or agrochemicals, generates changes in populations of soil arthropods. Reduce handling the growing area can maintain greater diversity of beneficial arthropods. The main objective of this study was to evaluate the abundance and diversity of soil arthropod communities in areas with No Tillage systems, Minimum Tillage, Conventional Planting and native area of savanna (Água Boa) and Amazon rain forest (Serra da Prata) in Roraima. This is a randomized trial designed with four replications (plots of 10x10m), and four treatments in each area: No Tillage with rotation Soybean/Brachiaria, Minimum Tillage of Soybean/braquiaria, Conventional Soybean Planting and native area. Pitfall and Berlese type traps were installed in the center of each plot in the months of July and October 2015 and January and April of 2016. Arthropods collected in the traps were identified to the lowest possible taxonomic level. Areas and treatments were compared with aggrupation analysis in the program Past 3.13. The basis of the analysis was to analyze the population dynamics of the most abundant morphotypes treatment and performed by Pearson correlation with temperature and precipitation. Index of Simpson (D) and Pielou (E) for each treatment were calculated and subjected to ANOVA and Tukey test (p <0.05). A total of 8,839 arthropods were collected and identified in 116 morphotypes belonging to 17 orders and 45 families. The aggrupation analysis showed that at the beginning (July) and at the end (April) of the study, native and crop system areas differ from each other. By October and January, Minimum Tillage was the most different above the remaining treatments A greater abundance of Chrysomelidae and Oribatulidae planting systems for areas of Água Boa and Serra da Prata were collected respectively, (a similar distribution for all treatments Formicidae was observed). Pearson's correlation was only significant for the treatment of Native Area, No Tillage and Minimum Tillage in Água Boa and for Minimum Tillage and No Tillage in Serra da Prata. Simpson index showed significant difference between Native Area and Minimum Tillage in January 2016 in Água Boa.